Factors Affecting Potential Company Bankruptcy During The Covid-19 Pandemic - Rinofah, Risal; Kusumawardhani, Ratih; Maha Putri, Virginia Athadhita (Jurnal Keuangan dan Perbankan, 2022)
The Covid-19 pandemic that occurred has damaged the Economy of Indonesia and even the world. This poses a threat to companies in various sectors. Thus, this study aims to test the role of financial ratios (current ratio, debt to asset ratio, return on asset, total asset turnover, sales growth) and macroeconomic factors (inflation, exchange rate, interest rates, and economic growth) in predicting financial distress conditions in the pharmaceutical, telecommunications, hotel and restaurant, health, financing institutions listed on the Indonesia Stock Exchange, with the research model altman Z-Score Modification as measured by methods based on multiple linear regression. The data used in this study is secondary data, in the form of company financial statements taken quarterly for 2019-2020. The results proved that the current ratio, total asset turnover, sales growth had a significant positive effect in predicting financial distress. In contrast, the debt to asset ratio had a significant negative impact, while inflation, exchange rates, interest rates, and economic growth did not affect financial distress conditions.